Dietary clove (Syzygium aromaticum) powder enhanced broiler chicken performance, gut histomorphometry and health-associated whilst decreasing pathogenic microbiota - Ogwuegbu, M. C.; Uzochukwu, I. E.; Edeh, H. O.; Ukah, E. G.; Obey, C. O.; Okpanachi, U.; Mthiyane, D. M. N. (Diponegoro University, 2025)
This study evaluated the impact of dietary clove powder on growth performance, carcass traits, nutrient digestibility, jejunal histomorphometry and ileal microbiota in broiler chickens. A total of 250 Chikun day-old broiler chicks were allocated to 5 dietary groups with 5 replicates of 10 birds each for 6 weeks in a completely randomized design. The groups were fed diets containing clove powder at 0, 0.5, 1.0, 1.5 and 2 g/kg diet. Results showed that dietary clove supplementation improved final body weight and feed conversion ratio (P < 0.001) while reducing total feed intake. Also, it increased weights of live chickens at slaughter, breast meat, shank and drumstick/thigh ratio (P < 0.001). Further, it linearly increased apparent digestibility of DM, CP, and EE (P < 0.01) as it quadratically decreased CF (P < 0.01). Furthermore, it linearly increased jejunal villus length, crypt depth and thickness of muscularis (P < 0.001) whilst it quadratically decreased thickness of the epithelium (P < 0.01). Moreo-ver, it increased ileal Lactobacilli whilst decreasing Salmonella and E. coli (P < 0.05) bacterial species. In conclusion, dietary clove powder improved growth performance, carcass characteristics, nutrient digestibility, gut histomorphometry and Lactobacilli while it decreased Salmonella and E. coli bacteria.